Noise exposure and hearing threshold levels of rice mill workers - Rachmawati, Siti; Suryadi, Iwan; Fitriani, Nurlaila; Firmansyah, Fathoni; Nisya, Khoirun (International Journal of Public Health Science (IJPHS), 2025)
Industrial noise is generally one of the risk factors for occupational and environmental safety and health. Noise is a risk factor for decreased hearing threshold value in addition to other factors such as age, working period. This study used a cross-sectional design that aimed to identify the hearing threshold level (HTL) of rice mill workers exposed to hazardous noise in Karanganyar Regency, and investigate the relationship with other factors such as age, tenure. Audiometric data from 92 participants were collected through audiometric examination by qualified personnel using an audiometer in a quiet environment. The test was conducted after the participants had rested completely for >14 hours after their last exposure to workplace noise. The results showed that all participants had worked in a noise-hazard work zone for >1 year. The participants' ages ranged from 28 to 57 years. The average hearing threshold in the right ear was 36.71 dB and the average hearing threshold in the left ear was 39.55 dB. The hearing loss associated with work experience was greater than that caused by noise intensity age. Noise intensity, age and working experience were significant to the workers' ear hearing threshold values. Multivariate test results show that noise intensity is the most influential factor (>60%) on HTL. HTL among industrial workers should be assessed regularly. At the health policy level, these workers need to start being protected when they start working.